SARS‐Cov‐2 in peritoneal fluid: an important finding in the Covid‐19 pandemic. Issue 10 (20th July 2020) - Barberis, A.; Rutigliani, M.; Belli, F.; Ciferri, E.; Mori, M.; Filauro, M.
Fundings: no funding to declare regarding this study.